A lean, keen, kid-centred machine: change in children's ED. (26th December 2010) - Crew, Jamie
Abstract : Introduction: Our Children's Emergency Department, as part of a whole hospital improvement project has been piloting 'Lean Thinking' to develop and trial new ideas and processes within the department. Our initial project has been focusing on how we manage injuries in the department with the aim of 'developing a system whereby children with injuries can be seen more efficiently and effectively by having combined medical and nursing staff assessment and treatment, coupled with the ability to prescribe and make appointments during the same consultation.' Methods: We have used a series of lean processes and tools (Scope tools, KANO workshops, current state, process mapping, future state, ideas wall, Plan-Do-Study-Act (PDSA) cycle) to engage staff and facilitate them to generate ideas and develop projects for change and improvement. The initial priority for our Children's Emergency Department was the development of a multidisciplinary area in which to see and treat injuries. The idea was then developed into a clinical process and trialled, within the department, in real-time without any cessation of service. The findings are analysed, the processes refined, and further trials instituted to consolidate the process before full implementation. Results: We have completed three trials of the MDT injuries area with dramatic improvements in patient and staff satisfaction, as well as more objective outcomes one example being decreased patient journey. The average time from arrival to discharge in the trial was compared with baseline data for the same time over the preceeding 10 weeks:- Trial 1 (4 h) baseline 120 min, trial 30 min; Trial 2 (8 h) baseline 103 min, trial 54; Trial 3 (10 h) baseline 94 min, trial 49. We are now moving to implementation of this new area for 10 h a day, 7 days a week. Conclusion: Lean processes with real-time trials can facilitate successful, continuous, staff driven change within a Paediatric Emergency Department.